Vehicle Speed Estimation Using OpenCV Framework - Siva Lakshmi, Yenuganti; Navya Sri, Prathigudupu; Mounika, Siddi; Usha Sri, Tata; Suresh, Yallamati (International Journal of Computer Sciences and Engineering, 2023)
This article tracks and monitors vehicle speeds by utilizing computer vision techniques and libraries such as OpenCV and dlib. Using video inputs, it effectively recognizes vehicles, records their motions, and determines their speeds by calculating the time interval between frames and the distances they travel. In a CSV file, the gathered speed data is methodically documented and contains relevant details including timestamps, vehicle identities, and observed speeds in kilometers per hour. Another important element of the system is that it enforces a predetermined speed limit and sends out alarm messages to vehicles that go over it. This allows for real-time visual notifications that show the speed value and timestamp. Such a versatile system offers vital support in traffic management, traffic data analysis, and road safety enforcement, among its many possible use cases.